Sekuritisasi Penyebaran Virus Corona oleh Organisasi Kesehatan Dunia - Indra Tamsyah (Jurnal Ilmu Hubungan Internasional LINO, 2022)
Abstract: Covid-19 were discovered in Wuhan, China and turned into a pandemic illness that undermined individuals all over the planet. The spread of the infection has constrained the public authority in any nations to make new policies to safeguard their citizens. The presence of the Covid is a danger to each nation and this is a non-traditional issue. Non-traditional security problems can be turned into security problems through a securitization process. Covid is not a part of security isssue however, it can transform into a security issue since it is remembered for the class of wellbeing security and it is significant in keeping up with public safety. In this case study, the creator utilizes descriptive method with optional information assortment procedures or writing study, and furthermore securitization hypothesis to inspect the most common way of evolving non-security issue into security issue through five markers, thus are securitizing actor, speech act, existential treat, referent object/audience and extraordinary measure. Keywords: Security, Corona Virus, Securitization, World Health Organization Abstrak: Covid-19 ditemukan di Wuhan, Cina dan menjadi penyakit pandemi yang mengancam masyarakat di seluruh dunia. Penyebaran virus telah memaksa pemerintah di negara manapun untuk membuat kebijakan baru untuk melindungi warganya. Kehadiran virus corona adalah ancaman bagi setiap negara dan ini adalah masalah keamanan non-tradisional. Masalah keamanan non tradisional dapat diubah menjadi masalah keamanan melalui suatu proses sekuritisasi. Covid-19 bukan bagian dari masalah keamanan tapi bisa berubah menjadi masalah keamanan karena termasuk dalam kategori health security dan penting dalam menjaga keamanan nasional. Dalam studi kasus ini, penulis menggunakan metode deskriptif dengan teknik pengumpulan data sekunder atau studi pustaka, serta teori sekuritisasi untuk mengkaji proses perubahan isu non-keamanan menjadi isu keamanan melalui lima indikator yaitu aktor sekuritisasi, tindak tutur, ancaman eksistensial, objek rujukan/audiens dan ukuran luar biasa. Kata Kunci: Keamanan, Covid-19, Sekuritisasi, Organisasi Kesehatan Dunia